A direct replication and extension of Popp and Serra (2016, experiment 1): better free recall and worse cued recall of animal names than object names, accounting for semantic similarity - Mah, Eric Y.; Grannon, Kelly E. L.; Campbell, Alison; Tamburri, Nicholas; Jamieson, Randall K.; Lindsay, D. Stephen (Frontiers in Psychology, 2023)
Free recall tends to be better for names of animate concepts such as animals than for names of inanimate objects. Popp and Serra (2016) replicated this “animacy effect” in free recall but when participants studied words in pairs (animate-animate pairs intermixed with inanimate-inanimate pairs) and were tested with cued recall, performance was better for inanimate-inanimate pairs than for animate-animate pairs (“reverse animacy”). Our Experiment 1 was a preregistered direct replication (N = 101) of their Experiment 1 (mixed-lists condition). Just as in Popp and Serra, we observed an animacy effect for free recall and a reverse animacy effect for cued recall. Unlike Popp and Serra, we found that controlling for interference effects rendered the reverse animacy effect non-significant. We took this as evidence that characteristics of the stimulus sets (e.g., category structure, within-category similarity) may play a role in animacy and reverse animacy effects. In a second preregistered experiment conducted in four different samples (undergraduate N = 153, undergraduate N = 143, online Prolific N = 101, online Prolific/English-as-a-first-language N = 150), we manipulated the within-category semantic similarity of animal and object wordlists. In three out of these four samples, we observed reverse animacy effects when within-category similarity was higher for animals and when within-category similarity was equated for animals and objects. This suggests that semantic similarity alone cannot explain the reverse animacy effect.